THE EFFECT OF COMPETENCE, WORK MOTIVATION, LEADERSHIP AND COMPENSATION ON AFFECTIVE COMMITMENT AND IMPLICATIONS ON PERFORMANCE - Hermansyah, Taufik; Affandi, Azhar; Hermawan, Atang (Jurnal Riset Bisnis dan Manajemen, 2024)
This study aims to determine the effect of Competence, Work Motivation, Leadership and Compensation on Affective Commitment and Implications for Agent Performance in Branchless Banking (Survey at BRI Banjarmasin Regional Office). The results of Descriptive research state that Competence is in the fairly good category with the highest dimension is Knowledge, while the lowest dimension is Transfer Skill. Work motivation is in the fairly high category. Leadership is in the category of quite effective. Compensation is in the fairly high category. Affective commitment is in the category of quite strong. The performance is in the fairly high category, while the lowest dimension is Quality. The results of the Verification have a significant influence on the variables of Competence, Work Motivation, Leadership and Compensation simultaneously on Affective Commitment and have an impact on the performance.